Measurement Techniques for the Investigation of the Primary Atomization of Fuel Sprays - Durst, Alexander; Wensing, Michael; Gröger, Karsten; Kawaharada, N.; Dinkelacker, Friedrich; Wang, Jin (Workshop ENCOM 2019, Waischenfeld, 16./17.10.2019, 2019)
The mixture formation of modern combustion engines is one key element to increase the efficiency and lower the exhaust emissions. Therefore, the spray atomization process has to be understood in detail, because it is the basis of the following secondary atomization and evaporation of the spray. Due to very high optical densities and velocities of the fuel spray in the first millimetres after the nozzle orifice, detailed measurements are a challenge. Within a cooperative project of the ITV Hannover and the LTT Erlangen different measurement techniques are developed and compared for this spray area for diesel injectors, including measurements with synchrotron radiation at the ANL in Chicago and spray velocity measurements at the Nagasaki University in Japan. A great effort was taken to ensure a high comparability of the measurement results from different facilities by using the same operating conditions and the same injector for all measurements. With this, the capability of the measurement techniques to measure the primary atomization was tested. Three main characteristics (structure, mass, and velocity) were evaluated describing the spra